Antimicrobial and Anti-Inflammatory Bioactive Peptides: Their Role in Potential Therapeutic Applications for Periodontitis—A Narrative Review - Tonolo, Federica; Silva, Renata Cristina Lima [UNESP]; Bortoluzzi, Mary; Scarel-Caminaga, Raquel Mantuaneli [UNESP]; Vianello, Fabio (MDPI, 2025)
Bioactive peptides have garnered increasing interest in recent years due to their potential applications in the medical field, for example, as promising adjuvant therapeutic agents to modulate the host immune response and counteract microbial dysbiosis in chronic pathologies. Primarily derived from protein hydrolysates of food waste, these components exhibit beneficial properties, such as anti-inflammatory, antimicrobial, antioxidant, and antidiabetic effects. This narrative review focuses on bioactive peptides with antimicrobial and anti-inflammatory properties, highlighting their mechanisms of action, sources, and therapeutic potential in the context of chronic conditions, particularly periodontal disease, especially when comorbidities are present (i.e., type 2 diabetes mellitus). The mechanisms of action and sources, as well as preclinical and clinical studies evaluating bioactive peptides efficacy, are discussed. Further research is warranted to establish their clinical viability and integration into conventional therapeutic strategies.